2022
DOI: 10.1029/2021jc018074
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Interannual Patterns of Epipelagic Summer Mesozooplankton Community Structures in the Western Arctic Ocean in 2016–2020

Abstract: Mesozooplankton play a crucial role as primary or secondary consumers in Arctic ecosystems and are sensitive indicators of environmental changes. This research is the first comprehensive Arctic zooplankton study covering the area ranging from the southern Chukchi Sea (SCS) and the northern Chukchi Sea (NCS) to the East Siberian Sea (ESS). Mesozooplankton samples were collected at 151 stations in the western Arctic Ocean each August from 2016 to 2020. The mesozooplankton abundance of the study area ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(154 reference statements)
1
4
0
Order By: Relevance
“…Species transportation from the Atlantic and East Siberian regions in this study is consistent with the findings of Wisz et al (2015), who argued that transfers from the Atlantic to the Pacific Ocean would be primarily facilitated through the Northwest Passage. This phenomenon has been confirmed in various taxa (Beaugrand et al, 2002;Perry et al, 2005;Reid et al, 2007;Wisz et al, 2015;Kim et al, 2020, Kim et al, 2022. However, Gadus macrocephalus, another dominant species in the Pacific sub-Arctic regions, has not been observed in this survey although this species is also known as extending their distribution northward (Stevenson and Lauth, 2019;Baker, 2021;Cooper et al, 2023).…”
Section: Discussionsupporting
confidence: 66%
“…Species transportation from the Atlantic and East Siberian regions in this study is consistent with the findings of Wisz et al (2015), who argued that transfers from the Atlantic to the Pacific Ocean would be primarily facilitated through the Northwest Passage. This phenomenon has been confirmed in various taxa (Beaugrand et al, 2002;Perry et al, 2005;Reid et al, 2007;Wisz et al, 2015;Kim et al, 2020, Kim et al, 2022. However, Gadus macrocephalus, another dominant species in the Pacific sub-Arctic regions, has not been observed in this survey although this species is also known as extending their distribution northward (Stevenson and Lauth, 2019;Baker, 2021;Cooper et al, 2023).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that macrozooplankton abundance and biomass increase significantly in warmer waters in recent years compared to historical studies ( Ershova et al, 2015 ; Xu et al, 2018 ; Kim et al, 2022 ). During each August from 2016 to 2020, macrozooplankton abundance was highest in the Bering Strait with higher water temperature ( Kim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that macrozooplankton abundance and biomass increase significantly in warmer waters in recent years compared to historical studies ( Ershova et al, 2015 ; Xu et al, 2018 ; Kim et al, 2022 ). During each August from 2016 to 2020, macrozooplankton abundance was highest in the Bering Strait with higher water temperature ( Kim et al, 2022 ). As important food items of macrozooplankton, we speculate that higher ciliate abundance and biomass in warmer waters of 2019 might be the main reason for higher macrozooplankton abundance.…”
Section: Discussionmentioning
confidence: 79%
“…The August mean nitrate concentration in the upper SCM depth was highest in 2019 (Figure 4B) and is unlikely to be a limiting factor for phytoplankton growth. Grazing pressure at higher trophic levels is likely to be one of the limiting factors for phytoplankton in 2019, as the mesozooplankton abundance was reported to be slightly higher in August 2019 than in August 2018 in the west (Kim et al, 2022). Finally, the mean daily insolation was lowest in 2019 (average 184 mEm -2 d -1 ) in the six-year survey.…”
Section: Limiting Factors For Phytoplankton Distributionmentioning
confidence: 91%
“…However, the effects of these environmental changes on marine phytoplankton remain poorly understood. Although previous studies have reported data on chlorophyll-a (chl-a) concentrations in the NCESS during specific periods, these data have been used primarily as variables to explain the results in the fields of phytoplankton physiology, marine ecology, and biogeochemistry (Ko et al, 2020;Jung et al, 2021;Kim et al, 2022;Ko et al, 2022). To explore how large-scale climate and local physical forcing affect phytoplankton biomass and communities in the NCESS, we investigated the multi-year (2015)(2016)(2017)(2018)(2019)(2020) distributions of summer (August) chl-a concentrations and size structures using data collected by the Korea-Arctic Ocean Observing System (K-AOOS) program.…”
Section: Introductionmentioning
confidence: 99%